The Hybrid Contracts in Trade Finance and Letters of Credit Against Multipurpose Financing - Yustika Pratiwi, Hamlatussa’adah; Herdiana Abdurrahman, Nana; Prasetyo, Yoyok (Yayasan Mentari Madani, 2024)
The concept of